Impact of Mobile Apps Development on Self-Management of Weight Loss: Case of LPM Mobile App - Kukadiya, Lavkumar (Digital Repository of Theses, 2025)
When excess calories are not burned through physical activity and are instead deposited as fat in the body, the condition is known as obesity. Consuming foods high in fat and sugar, which have a lot of calories, might cause it. Sustaining a healthy BMI and controlling body weight are mostly dependent on diet. Consuming a lot of fast food or processed foods might cause the body to gain excess fat. It could also be brought on by inadequate levels of physical activity, excessive amounts of stress, or shifting surroundings. The purpose of the dissertation is to highlight how mobile app development affects weight loss self-management. The study demonstrated the increasing contributing factors to obesity and overweight conditions, particularly in youngsters and growing adults, using data from the LPM mobile app. To comprehend the link between the impact of weight loss management mobile applications on the self-management of weight loss among obese people, an investigation of the LPM mobile app has been conducted. For obese people, following a disciplined and methodical weight loss plan is crucial to getting the most effective outcomes. Additionally, the study described the prevalence of obesity worldwide in various nations. A questionnaire approach was utilised to get relevant data from people who are attempting to lose weight by utilizing the LPM mobile application to accomplish the study goals. The study findings suggested that when it comes to assisting people in losing weight, mobile applications are often more successful than small intervention groups and can be on par with or even more successful than traditional paper-and-pencil weight loss therapy. Numerous behaviours, including peer support, educational resources, and monitoring of a person's weight, activity level, and diet, are promoted by apps for smartphones. Because app types differ greatly, it can be difficult to identify the components that are most crucial to the program's accomplishment. The effectiveness of the program is based on how much the patients use the application on their mobile devices. Smartphone apps can help people lose weight and are a useful, cost-effective alternative to intense in-person weight loss programs. More research is necessary to ensure their long-term viability, especially for hard-to-reach groups. Keywords: Mobile Apps Development, self-management, weight loss, LPM Mobile apps, Obesity, Overweight